Character and role of the state from a governance perspective - Vili, Ongezwa (University of the Free State, 2023)
In 1994, South Africa left behind its unequal and racist past, ushering in a new system of democracy that brought hope for a brighter future for its citizens. This new system was meant to bring and advocate for equality, job opportunities, the eradication of poverty and freedom; however, it seems that many South Africans are still plagued by the same issues they faced in the past. Most citizens are still experiencing poor service delivery in their communities, such as in the townships and rural areas, and unemployment remains a problem, as is corruption (Masiya, Davids & Mangai, 2019). The Finance Minister, Tito Mboweni, stated in his May 2021 Budget Vote debate that 163 municipalities were in financial distress and 40 in financial and service delivery crises. Moreover, 102 municipalities adopted budgets they could not fund. Mboweni concluded, “It is indeed lamentable that the trajectory of municipal performance is unimpressive. Much of the progress made has been eclipsed by the widespread ‘failure’ of many municipalities. Rather than moving communities forward, many municipalities have themselves regressed.” Lastly, Merton (2021) argues that ineffective political leadership, characterised by conflict among council members and undue political intervention in administrative affairs, has hindered the development of a functional municipal sector. One would assume that the local sphere of government would know and ensure the quality of service delivery as it is closest to communities; however, that is not the case in some South African municipalities. This study will begin with a definition of the state, which will help to establish the role and character of the state as it is one of the underlying concepts of this study. Furthermore, this study will define ‘effective government’ to analyse or establish to what degree the South African government has been effective in addressing the issues or challenges faced by its citizens in the new democracy since 1994.
Dissertation(M.A.(Governance and Political Transformation))--University of the Free State, 2023
Keywords: South Africa; South African municipalities; New system of democracy; Challenges; Poor service delivery; Corruption; Quality of service delivery; ‘Effective government’